OPTIMASI KONTRIBUSI PEMBIAYAAN SYARIAH PADA USAHA MIKRO KECIL DAN MENENGAH DI BANK SYARIAH MANDIRI - Fajar Pasaribu (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The data collection technique used is the technique dokumentasi.Penulis using descriptive analysis in analyzing the data. The results showed that the financing disbursed by Bank Syariah Mandiri in an increase in micro, small and medium enterprises (SMEs) is not optimal. This is because (1) a relatively small share of Islamic banking, (2) lack of qualified human resources, (3) the paradigm of conventional banks is still strong, (4) lack of socialization, and (5) the limited network. Therefore, to optimize the role of Sharia Bank independently in the development of SMEs carried out cooperation in channeling funding to the concept of linkage with LKM / S, RB / S, BMT, KJKS / UJKS and Non Bank Financial Institutions other, enhance capacity building SME customers and partners linkage to be more capable and able to thrive in serving SME customers, in cooperation with the government financing program to get a guarantee facility, liquidity or other assistance. Their partnership with great entrepreneurs in partnership Inti-Plasma, opening outlets Micro with Micro Shop BSM brand, developing a monitoring system based small micro-finance technology to streamline and lower the cost of financing monitoring.